Preparation method of organic silicon antifouling coating of slow-release lubricant

By grafting specific polymers on the surface of silica nanoparticles and introducing lubricating oil using emulsion polymerization technology, the problem of poor anti-fouling performance of silicone anti-fouling coating in static environments is solved, and high adhesion and good mechanical properties are achieved And long-term anti-fouling effect.

CN119391292APending Publication Date: 2025-02-07郑州轻大产业技术研究院有限公司 +1

Patent Information

Application Number
CN202411673884.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing silicone antifouling coating has poor antifouling performance in static environments and is insufficient in adhesion and mechanical properties with the substrate.

Method used

By grafting acryloyloxyalkylalkoxysilane and fluoro-containing acrylate on the surface of silica nanoparticles and using hydrolytic crosslinking of multiple Si-O of Si-N-bonded organosiloxanes, a formation of Functional nanoparticles, combined with emulsion polymerization technology, introduce lubricating oil into the coating in the form of emulsion particles to achieve long-term sustained release of lubricating oil.

Benefits of technology

It improves the adhesion and mechanical properties of the coating and the substrate, enhances the hydrophobic and oleophobic properties of the coating, improves the anti-fouling ability, and maintains the adhesion strength during the long-term release of lubricating oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391292A_ABST
    Figure CN119391292A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic silicon coatings, in particular to a preparation method of an organic silicon antifouling coating for slowly releasing a lubricant. The preparation method of the organosilicon antifouling coating of the slow-release lubricant comprises the following steps: carrying out emulsion polymerization on silicon dioxide nanoparticles, acryloyloxy alkyl alkoxy silane, fluorine-containing acrylate and lubricating oil in a redox system to obtain a fluorine-silicon modified silicon dioxide nanoparticle emulsion of which the surface is attached with the lubricating oil; and then mixing with organic silicon resin, a coupling agent, a cross-linking agent and a catalyst, and carrying out cross-linking curing to obtain the organic silicon coating. The lubricating oil is adsorbed on the surfaces of the nano particles under the action of grafted functional groups of the functionalized nano particles, so that the lubricating oil is introduced into the organic silicon coating in the form of emulsion particles, micro-nano lubricating oil droplets are formed, long-acting slow release of the lubricating oil is realized, the amphiphobic property and low surface energy of the coating are improved, and the antifouling capacity of the coating is improved; meanwhile, the mechanical property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organosilicon coatings, and in particular to a method for preparing an organosilicon antifouling coating with a slow-release lubricant. Background Art

[0002] Silicone coating is a well-known elastomeric hydrophobic material with low surface free energy and low elastic modulus. However, it has the problem of poor static antifouling effect. In a static environment, due to its surface hydrophobicity, it will adsorb microorganisms such as diatoms to form a fouling film, which reduces the antifouling effect. According to studies, it is difficult to remove fouling such as algae mud adsorbed on the surface of high-speed ships. Therefore, the focus of polydimethylsiloxane (PDMS) is to improve its fouling release performance.

[0003] In order to solve the problem of poor static antifouling performance of organic silicon antifouling coating, it is necessary to modify it. Physical or chemical modification methods can be used to improve the performance of organic silicon coating in a targeted manner. The main modification methods of organic silicon coating are: amphiphilic modification, fluorocarbon resin modification, super lubricity modification, etc., which can enhance its fouling release or fouling resistance while retaining the low surface energy characteristics of organic silicon coating, and at the same time make the coating have good stability and lasting antifouling performance.

[0004] Due to its unique oil layer protection, the super-lubricating coating can effectively prevent the attachment of fouling organisms to the coating surface and reduce the harm caused by fouling organisms. However, the failure of the coating caused by the easy loss of lubricating oil is a common problem of super-lubricating coatings. The prior art introduces lubricating oil into the coating so that the coating continuously releases new oil and preserves the liquid oil film on the surface. When it encounters environmental damage, the elastic behavior of the coating will accelerate the replenishment of the oil film to form an autocrine super-lubricating coating. For example, a Chinese patent application with application publication number CN109453966A, which was applied for and published on March 12, 2019, discloses a long-term protective liquid autocrine super-lubricating coating and a preparation method. First, an elastic porous membrane layer with a porous structure is prepared, and the prepared coating is immersed in lubricating oil in a water bath at 50 to 80°C and allowed to stand for 2 to 12 hours. The lubricating oil includes perfluoropolyether, silicone oil, mineral oil, ionic liquid, animal and vegetable oil, and long-chain alkane. The material of the elastic porous membrane layer includes silica gel, latex, Polyurethane, rubber, viscoelastics, etc., to obtain a self-secreting super-slip coating, which is divided into a bottom layer, an upper layer and a surface layer. The large pore structure of the bottom layer (pore size range 100μm ~ 2000μm) increases the oil storage capacity, the medium pore structure of the upper layer (10nm ~ 100μm) prevents the oil from losing too fast and controls the secretion process. The micro-nano-level convex structure of the surface layer plays a role in liquid-repellent oil storage. The lubricating oil is stored in the porous structure. When the surface oil dries up, it can gradually diffuse to the surface through the upper pores to form a liquid protective oil film. When the surface oil film is lost due to strong external forces such as water flow impact, wind, vibration, external friction, etc. during the service of the coating, the high elasticity of the coating will release the oil layer in the pores under pressure, and the coating surface will still maintain a stable oil film.

[0005] However, the large droplets of lubricating oil in the above-mentioned autocrine super-slip coating will reduce the adhesion between the coating and the substrate, affecting the protective performance of the coating. In addition, the mechanical properties of silicone materials themselves are poor, and the integrity of the paint film is easily destroyed in practical applications. Summary of the invention

[0006] The invention provides a method for preparing an organosilicon antifouling coating of a slow-release lubricant, which solves the problems of poor adhesion between the existing organosilicon coating of slow-release lubricant and a substrate and poor mechanical properties.

[0007] In order to solve the above technical problems, the technical solution of the method for preparing the organic silicon antifouling coating of the slow-release lubricant of the present invention is as follows:

[0008] A method for preparing a slow-release lubricant organic silicon antifouling coating comprises the following steps:

[0009] 1) silica nanoparticles, acryloxyalkylalkoxysilane, fluorinated acrylate, and lubricating oil are subjected to emulsion polymerization or core-shell emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds under the action of an emulsifier to obtain a fluorine-silicon-modified silica nanoparticle emulsion with lubricating oil attached to the surface;

[0010] 2) The fluorosilicone-modified silica nanoparticle emulsion with lubricating oil attached to the surface obtained in step 1) is mixed with an organosilicon resin, a coupling agent, a crosslinking agent and a catalyst to obtain an organosilicon coating, which is applied to a substrate and crosslinked and cured to obtain an organosilicon antifouling coating with a slow-release lubricant.

[0011] The present invention is an improvement on the prior art, and provides a method for preparing an organic silicon antifouling coating of a slow-release lubricant. Acryloxyalkylalkoxysilane and fluorine-containing acrylate are grafted on the surface of silicon dioxide by emulsion polymerization or core-shell emulsion polymerization, and the polymerized acrylic acid-containing chain segments are connected into a network by hydrolysis cross-linking of multiple Si-O groups of organic silicon oxane containing Si-N bonds, and cross-linked with hydroxyl groups on the surface of silicon dioxide, thereby initiating polymerization on the surface of silicon dioxide, thereby realizing the functionalization of silicon dioxide nanoparticles; at the same time, by utilizing the emulsification effect and the amphiphobicity of the functionalized nanoparticles, lubricating oil is adsorbed on the surface of the functionalized nanoparticles, and introduced into the organic silicon coating in the form of emulsion particles, forming micro-nano-scale lubricating oil droplets, and the long-term slow release of the lubricating oil is realized by penetration between organic silicon molecular chains.

[0012] Compared with the organic silicon coating introduced with lubricating oil in the form of large droplets, the organic silicon antifouling coating obtained by the present invention can improve the adhesion between the coating and the substrate by introducing the lubricating oil in the form of emulsion particles, and the adhesion strength reaches 0.89MPa; at the same time, the functionalized nanoparticles can improve the hydrophobicity and oleophobicity of the coating (amphiphobicity of the coating), the water contact angle reaches more than 116°, the diiodomethane contact angle reaches more than 95°, and has a lower surface energy, as low as 11mJ m -2 The following works synergistically with the slow-release lubricant to improve the anti-fouling ability of the coating; the mechanical properties of the coating are improved, and the tensile strength of the coating reaches above 0.5 MPa. While reducing the surface energy of the organic silicon coating, the mechanical properties of the coating are improved, and the organic silicon coating of the present invention can still maintain its adhesion strength without reduction during the long-term release of the lubricant.

[0013] The present invention performs emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds, and uses an organosilicon compound containing silicon-nitrogen bonds and ammonium persulfate as redox initiators, so that the polymerization reaction can be carried out in an aqueous phase without the need to react in an organic solvent. The reaction can be carried out at room temperature and is easy to control. The product of the emulsion polymerization is not easy to agglomerate and the reaction time is short.

[0014] In order to further increase the density of grafted functional groups of silica nanoparticles and improve the adsorption effect on lubricating oil, preferably, the molar ratio of the acryloxyalkylalkoxysilane and the fluorinated acrylate is (2.5-3):(4.5-5), and the mass ratio of the silica nanoparticles, acryloxyalkylalkoxysilane and lubricating oil is (0.9-1):(7-8):(12-14).

[0015] In order to further improve the properties of the copolymer grafted on the surface of the silica nanoparticles, so as to improve the surface energy and mechanical properties of the coating and enhance the adsorption of lubricating oil, preferably, the acryloxyalkylalkoxysilane is γ-methacryloxypropyltrimethoxysilane, the fluorine-containing acrylate is dodecafluoroheptyl methacrylate, and the lubricating oil is selected from one or both of methyl silicone oil and perfluoropolyether lubricating oil.

[0016] In order to further improve the mechanical properties of the organosilicon coating and the adhesion to the substrate, preferably, the mass ratio of the organosilicon resin to the silicon dioxide nanoparticles is (90-100): (0.9-1).

[0017] In order to further reduce the start-up energy of emulsion polymerization, preferably, the organosiloxane containing Si-N bonds has a structure shown in Formula I:

[0018]

[0019] In Formula I, R1, R2, R3, R 10 , R 11 and R 12 Each is independently selected from C1-C5 alkyl; R4 and R5 are each independently selected from C1-C6 alkylene; R6, R7, R8 and R9 are each independently selected from methyl, ethyl or propyl;

[0020] The persulfate is selected from one or more of ammonium persulfate, potassium persulfate and sodium persulfate.

[0021] In order to further reduce the start-up energy of emulsion polymerization, preferably, the mass ratio of the Si-N bond-containing organosiloxane to the persulfate is (1.5-2):(0.1-0.5), and the added amount of the Si-N bond-containing organosiloxane is 20-25% of the mass of the acryloxyalkylalkoxysilane.

[0022] In order to further improve the initiation rate during the emulsion polymerization, preferably, an alkali metal salt is introduced as a promoter during the emulsion polymerization or core-shell emulsion polymerization in step 1), wherein the alkali metal salt is selected from one or more of calcium chloride, sodium chloride and lithium chloride, and the amount of the alkali metal salt added is 0.8-1% of the mass of the acryloxyalkylalkoxysilane. The alkali metal salt can stabilize the free radicals generated in the water phase during the emulsion polymerization and improve the initiation rate.

[0023] In order to further reinforce the organosilicon coating, preferably, fumed silica with a particle size of 8 to 16 nm is added during mixing in step 2), and the mass ratio of the organosilicon resin to the fumed silica is (90 to 100): (4 to 4.5).

[0024] In order to further improve the curing efficiency of the silicone coating, preferably, in step 2), the mass ratio of the silicone resin, coupling agent, crosslinking agent and catalyst is (90-100): (1.8-3): (9-10): (0.2-0.4).

[0025] In order to further improve the curing efficiency of the silicone coating, preferably, the coupling agent in step 2) is 3-aminopropyltriethoxysilane and aminosilane polymer; the cross-linking agent is vinyltrimethoxysilane; the catalyst is dibutyltin dilaurate; and the mass ratio of 3-aminopropyltriethoxysilane to aminosilane polymer is (0.9-1.5):(0.9-1.5). BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a reaction principle diagram of SiO2-SiF@oil in Example 1 of the present invention;

[0027] Figure 2 This is a photo of a coating formed by applying the organosilicon coating of Example 1 of the present invention on a cement board;

[0028] Figure 3 FT-IR spectrum of SiO2-SiF@oil of Example 1 of the present invention;

[0029] Figure 4 TEM image of SiO2-SiF@oil of Example 1 of the present invention;

[0030] Figure 5 The organic silicon coating of Example 1 of the present invention and the contact angle test photograph after being placed for 7 days;

[0031] Figure 6 1 is a stress-strain curve diagram of the organic silicon coating of Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The technical concept of the method for preparing the slow-release lubricant organic silicon antifouling coating of the present invention is as follows:

[0033] The existing technology introduces lubricating oil into the coating by immersing a silicone coating with a porous structure in lubricating oil, thereby obtaining a self-secreting super-lubricating coating. The lubricating oil gradually diffuses to the surface through the pore structure to form a liquid protective oil film, thereby achieving the slow release of the lubricating oil. The super-slippery surface inhibits the attachment of microorganisms, thereby achieving long-term anti-fouling of the coating.

[0034] The present invention utilizes the effect of the grafted functional groups of functionalized nanoparticles to adsorb the lubricating oil on the surface of the nanoparticles, so that the lubricating oil is introduced into the organosilicon coating in the form of emulsion particles, forming micro-nano-scale small droplets of lubricating oil, and realizing long-term sustained release of the lubricating oil. Compared with the organosilicon coating that introduces the lubricating oil in large droplets, it can improve the adhesion between the coating and the substrate; and the grafted functional groups, while reducing the surface energy of the organosilicon coating, synergistically work with the sustained-release lubricating oil to further improve the anti-fouling ability of the coating and improve the mechanical properties of the coating.

[0035] The preparation method of the organic silicon antifouling coating of the slow-release lubricant of the present invention is specifically as follows: 1) after mixing a water dispersion of silicon dioxide nanoparticles, an emulsifier aqueous solution, lubricating oil, acryloxyalkylalkoxysilane and a fluorine-containing acrylate, respectively adding dropwise an organic siloxane containing Si-N bonds, a persulfate and an alkali metal salt aqueous solution under stirring conditions, and obtaining fluorine-silicon-modified silicon dioxide nanoparticles with lubricating oil attached to the surface after emulsion polymerization; 2) after mixing the fluorine-silicon-modified silicon dioxide nanoparticles with lubricating oil attached to the surface obtained in step 1), an organic silicon resin, fumed silica, a coupling agent, a crosslinking agent and a catalyst to obtain an organic silicon coating, and after coating on a substrate, crosslinking and curing, obtaining an organic silicon antifouling coating of the slow-release lubricant.

[0036] It is understandable that step 1) can also be core-shell emulsion polymerization, and the specific method is: after mixing the silica nanoparticle aqueous dispersion, emulsifier aqueous solution, lubricating oil, and acryloxyalkylalkoxysilane, respectively, under stirring conditions, an organic siloxane containing Si-N bonds, a persulfate, and an alkali metal salt aqueous solution are added dropwise to carry out a first emulsion polymerization, after the first emulsion polymerization is completed, a fluorine-containing acrylate is added, and under stirring conditions, an organic siloxane containing Si-N bonds, a persulfate, and an alkali metal salt aqueous solution are added dropwise to carry out a second emulsion polymerization to obtain fluorine-silicon-modified silica nanoparticles with lubricating oil attached to the surface.

[0037] In a specific embodiment, the emulsifier is OP-20, and the mass ratio of acryloxyalkylalkoxysilane to the emulsifier is (7-8):(0.9-1).

[0038] In a specific embodiment, the concentration of the silica nanoparticle aqueous dispersion is 2.5-3%; the concentration of the emulsifier aqueous solution is 9-10%.

[0039] In a specific embodiment, the emulsion polymerization reaction time is 1 to 2 hours.

[0040] In a specific embodiment, in step 2), fumed silica with particle sizes of 8 nm and 16 nm is added during mixing, and the mass ratio of fumed silica with particle sizes of 8 nm and 16 nm is (2-2.25):(2-2.25).

[0041] The organosiloxane containing Si-N bonds is prepared according to the method described in patent CN115490805A.

[0042] In a specific embodiment, the organosiloxane containing Si-N bonds is TBPDD, and the chemical formula of TBPDD is as follows:

[0043]

[0044] In a specific implementation manner, the organic silicon resin used is methyl-terminated 107 silicone rubber with a viscosity of 1000 to 15000 Pa·s.

[0045] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.

[0046] 1. Specific embodiment of the method for preparing the organic silicon antifouling coating of the slow-release lubricant of the present invention

[0047] Example 1

[0048] The preparation method of the organic silicon antifouling coating of the slow-release lubricant of this embodiment is as follows:

[0049] 1) 0.9 g SiO2 and 0.94 g emulsifier were dissolved in 35 g and 10 g water to form SiO2 aqueous dispersion and OP-20 aqueous solution respectively. The SiO2 aqueous dispersion and OP-20 aqueous solution were mixed with 12.73 g methyl silicone oil (PDMS), 7.45 g γ-methacryloxypropyltrimethoxysilane (γ-MPS), and 18 g dodecafluoroheptyl methacrylate (DMFA). After emulsification by an emulsifier, the mixture was added to a three-necked bottle. At a certain stirring speed, 0.1 g ammonium persulfate and 2 g aqueous solution of 0.06 g calcium chloride and 1.5 g TBPDD were added dropwise respectively. The reaction was continued for 1 h. The reaction principle is as follows: Figure 1 As shown, a fluorine-silicon modified silica nanoparticle emulsion with silicone oil attached to the surface was obtained, which was recorded as SiO2-SiF@oil emulsion;

[0050] 2) 2.25 g of 8 nm fumed silica, 2.25 g of 16 nm fumed silica, 2.7 g of SiO2-SiF@oil emulsion obtained in step 1) were mixed with 90 g of methyl-terminated 107 silicone rubber (viscosity of 1500 Pa·s), stirred at 15000 r / min for 5 min using a Fluke disperser, 0.9 g of 3-aminopropyltriethoxysilane and 0.9 g of aminosilane polymer (Zhejiang Boiling Point Chemical Co., Ltd., R-8104), 9.9 g of vinyltrimethoxysilane and 0.25 g of dibutyltin dilaurate were added, and stirring was ensured for 2 min after each addition of an auxiliary agent, and finally an organosilicon coating was prepared. After vacuum degassing in a vacuum oven, it was applied to a cement board and cross-linked and cured in air at room temperature to obtain a nano-silica composite organosilicon coating. The coating photo is shown in FIG. Figure 2 shown.

[0051] 2. Comparison

[0052] Comparative Example 1

[0053] The preparation method of the organic silicon coating of this comparative example is basically the same as that of Example 1, except that: in step 2), no SiO2-SiF@oil emulsion is introduced to obtain an organic silicon coating without silicon dioxide nanoparticle filling.

[0054] Comparative Example 2

[0055] The preparation method of the organic silicon coating of this comparative example is basically the same as that of Example 1, except that methyl silicone oil is directly introduced into the organic silicon coating. The specific method is:

[0056] 1) 0.9 g SiO2 and 0.94 g emulsifier were dissolved in 35 g and 10 g water to form SiO2 aqueous dispersion and OP-20 aqueous solution, respectively; the SiO2 aqueous dispersion, OP-20 aqueous solution, 7.45 g γ-methacryloxypropyltrimethoxysilane and 18 g dodecafluoroheptyl methacrylate were mixed, emulsified by an emulsifier and added to a three-necked bottle; 0.1 g ammonium persulfate and 2 g aqueous solution of 0.06 g calcium chloride and 1.5 g TBPDD were added dropwise at a certain stirring speed, respectively, and the mixture was reacted for 1 h to obtain a fluorine-silicon-modified silica nanoparticle emulsion, which was recorded as SiO2-SiF emulsion;

[0057] 2) 2.25 g of 8 nm fumed silica, 2.25 g of 16 nm fumed silica, 2.7 g of SiO2-SiF emulsion obtained in step 1), 90 g of methyl-terminated 107 silicone rubber (viscosity of 1500 Pa·s), and 12.73 g of methyl silicone oil were mixed, stirred at 15000 r / min for 5 min using a Fluke disperser, 0.9 g of 3-aminopropyltriethoxysilane and 0.9 g of aminosilane polymer (Zhejiang Boiling Point Chemical Co., Ltd., R-8104), 9.9 g of vinyltrimethoxysilane and 0.25 g of dibutyltin dilaurate were added, and stirring was performed for 2 min after each addition of an auxiliary agent, and finally an organosilicon coating was prepared. After vacuum degassing in a vacuum oven, the coating was applied to a cement board to be cross-linked and cured in air at room temperature to obtain an organosilicon coating.

[0058] 3. Experimental Examples

[0059] Experimental Example 1

[0060] This experimental example characterizes the SiO2-SiF@oil obtained in Example 1. Figure 3 FT-IR spectrum of SiO2-SiF@oil. Figure 3 It can be seen that 1716cm -1 、1640cm -1 、1085cm -1 、692cm -1 The characteristic peaks at 1012cm belong to C=O, NH, Si-O-Si and CF, respectively, indicating that acryloxyalkylalkoxysilane and fluorinated acrylate were successfully introduced on the SiO2 surface. -1 The appearance of the characteristic peak of Si-OCH3 indicates the presence of silicone oil.

[0061] Figure 4 TEM image of SiO2-SiF@oil. Figure 4 It can be clearly seen that tiny methyl silicone oil droplets are adsorbed on the surface of the functionalized particles.

[0062] Experimental Example 2

[0063] This experimental example characterizes and tests the performance of the silicone coating.

[0064] The contact angle test was used to evaluate the hydrophobicity and oleophobicity of the silicone coating and the coating after being placed in the air at room temperature for 7 days. The surface energy of the coating and the adhesion of the silicone coating to cement were tested. The adhesion test method was based on the standard ASTM D4541-09. The test results of water contact angle, diiodomethane contact angle, surface energy and adhesion strength are shown in Table 1. The contact angle test photos are shown in Figure 5 As shown, Figure 5a and c are photos of the water contact angle of the silicone coating of Example 1 and after being placed for 7 days, respectively. Figure 5 b and d are the diiodomethane contact angle photographs of the silicone coating of Example 1 and after being placed for 7 days, respectively.

[0065] Table 1 Contact angle and surface energy test results of coatings

[0066]

[0067] From Table 1 and Figure 5 It can be seen that compared with the organosilicon coating without introducing modified particles (Comparative Example 1), the adhesion strength of the organosilicon coating of the present invention is reduced because the organosilicon coating in Comparative Example 1 does not introduce silica filler, but the water contact angle and diiodomethane contact angle of the organosilicon coating of the present invention are increased to 116.85° and 95.76°, respectively, and the surface energy of the coating is reduced to 10.34 mJ m -2 , indicating that the introduction of SiO2-SiF@oil into the coating can improve the amphiphobicity of the organic silicon coating and reduce the surface energy of the coating, thereby slowing down the adhesion of contaminants on the coating, making it easier to remove the contaminants. Moreover, compared with the direct introduction of methyl silicone oil into the organic silicon coating (Comparative Example 2), the water and diiodomethane contact angles of the organic silicon coating of the present invention are increased, and the surface energy of the coating is lower, and the adhesion strength of the organic silicon coating is also greatly improved.

[0068] In addition, after the organic silicon coating of the present invention was placed for 7 days, the water contact angle and the diiodomethane contact angle remained basically unchanged, and the diiodomethane contact angle increased instead, and the surface energy was further reduced to 9.63 mJ m -2 , indicating that the methyl silicone oil adsorbed on the surface of the functionalized nanoparticles of the present invention can slowly seep out to achieve the sustained release of the lubricating oil.

[0069] The mechanical properties of the coating were characterized by tensile tests. A national standard sample of silicone material with a thickness of 2±0.2 mm was prepared according to GB / T1024.2-2006. The tensile speed was set to 50 mm / mm. The measured stress-strain curve was as follows: Figure 6 As shown, from Figure 6 It can be seen that, compared with the organosilicon coating without the introduction of modified particles, the breaking strength of the organosilicon coating of the present invention is greatly improved from 0.37 MPa to 0.52 MPa, and the breaking elongation is increased from 186% to 284%.

[0070] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a silicone antifouling coating with a slow-release lubricant, characterized in that: The following steps are involved: 1) silica nanoparticles, acryloxyalkylalkoxysilane, fluorinated acrylate, and lubricating oil are subjected to emulsion polymerization or core-shell emulsion polymerization in an organosiloxane / persulfate redox system containing Si-N bonds under the action of an emulsifier to obtain a fluorine-silicon-modified silica nanoparticle emulsion with lubricating oil attached to the surface; 2) The fluorosilicone-modified silica nanoparticle emulsion with lubricating oil attached to the surface obtained in step 1) is mixed with an organosilicon resin, a coupling agent, a crosslinking agent and a catalyst to obtain an organosilicon coating, which is applied to a substrate and crosslinked and cured to obtain an organosilicon antifouling coating with a slow-release lubricant.

2. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: The molar ratio of the acryloxyalkylalkoxysilane to the fluorine-containing acrylate is (2.5-3):(4.5-5), and the mass ratio of the silica nanoparticles, acryloxyalkylalkoxysilane and lubricating oil is (0.9-1):(7-8):(12-14).

3. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1 or 2, characterized in that: The acryloxyalkylalkoxysilane is γ-methacryloxypropyltrimethoxysilane, the fluorine-containing acrylate is dodecafluoroheptyl methacrylate, and the lubricating oil is selected from one or both of methyl silicone oil and perfluoropolyether lubricating oil.

4. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: The mass ratio of the silicone resin to the silicon dioxide nanoparticles is (90-100): (0.9-1).

5. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: The Si-N bond-containing organosiloxane has a structure shown in Formula I: In Formula I, R1, R2, R3, R 10 , R 11 and R 12 Each is independently selected from C1-C5 alkyl; R4 and R5 are each independently selected from C1-C6 alkylene; R6, R7, R8 and R9 are each independently selected from methyl, ethyl or propyl; The persulfate is selected from one or more of ammonium persulfate, potassium persulfate and sodium persulfate.

6. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1 or 5, characterized in that: The mass ratio of the organic siloxane containing Si-N bonds to the persulfate is (1.5-2):(0.1-0.5), and the added amount of the organic siloxane containing Si-N bonds is 20-25% of the mass of the acryloxyalkylalkoxysilane.

7. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: In step 1), an alkali metal salt is introduced as a promoter during emulsion polymerization or core-shell emulsion polymerization. The alkali metal salt is selected from one or more of calcium chloride, sodium chloride and lithium chloride. The amount of the alkali metal salt added is 0.8-1% of the mass of the acryloxyalkylalkoxysilane.

8. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: In step 2), fumed silica with a particle size of 8 to 16 nm is added during mixing, and the mass ratio of the silicone resin to the fumed silica is (90 to 100): (4 to 4.5).

9. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: In step 2), the mass ratio of the silicone resin, coupling agent, crosslinking agent and catalyst is (90-100): (1.8-3): (9-10): (0.2-0.4).

10. The method for preparing the organic silicon antifouling coating of the slow-release lubricant according to claim 1, characterized in that: The coupling agent in step 2) is 3-aminopropyltriethoxysilane and aminosilane polymer; the crosslinking agent is vinyltrimethoxysilane; the catalyst is dibutyltin dilaurate; the mass ratio of 3-aminopropyltriethoxysilane to aminosilane polymer is (0.9-1.5):(0.9-1.5).

Citation Information

Patent Citations

  • Long-acting protective liquid self-secreting super-lubricity coating and preparation method thereof

    CN109453966A

  • Lubricant-releasing material composition, lubricant-releasing material, production of lubricant-releasing membrane, lubricant-releasing membrane, member for fixation, fixing device, and color image formation

    JP1999071521A

  • In vitro diagnostic device for biometric information analysis based on imaging

    KR1020240017895A

  • Silicone (METH)acrylate particles, process for preparation thereof and use thereof

    US20090149573A1

  • Amphiphobic fluorine-containing nanofluid, preparation method therefor and application thereof

    WO2023083144A1

Cited By

  • Aerogel reinforced ship antifouling paint and preparation method thereof

    CN120682678A

  • Bionic fish scale composite coating with lubrication and resistance reduction performance and preparation method thereof

    CN121082529A

  • A biomimetic fish scale composite coating with lubrication and drag reduction properties and its preparation method

    CN121082529B